2021
DOI: 10.1038/s41434-021-00223-3
|View full text |Cite
|
Sign up to set email alerts
|

Use of CRISPR/Cas9-mediated disruption of CNS cell type genes to profile transduction of AAV by neonatal intracerebroventricular delivery in mice

Abstract: Adeno-associated virus (AAV) transduction efficiency and tropism are conventionally determined by high expression of a fluorescent reporter gene. Emerging data has suggested that such conventional methods may underestimate AAV transduction for cells in which reporter expression from AAV vectors is undetectable. To explore an alternative method that captures AAV transduction in cells in which low expression of a cargo is sufficient for the intended activity, we sought after CRISPR/Cas9-mediated gene disruption.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 52 publications
(10 reference statements)
0
13
0
Order By: Relevance
“…In particular, Gradinaru and colleagues have used the C re- re combination-based A AV-targeted e volution (CREATE) to isolate AAV9 variants, such as AAV-PHP.B and AAV-PHP.eB, which can efficiently bypass BBB and transduce the majority of adult brain neurons and astrocytes in certain mouse strains (Chan et al, 2017; Deverman et al, 2016). Both AAV-PHP.B and AAV-PHP.eB have been successfully used to deliver systemic gene expression (Liu et al, 2021; Luoni et al, 2020; Silva-Pinheiro et al, 2020), or target gene ablation by CRISPR/Cas9 across the adult mouse brain neurons (Torregrosa et al, 2021; Xiao et al, 2021; Yamaguchi and de Lecea, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Gradinaru and colleagues have used the C re- re combination-based A AV-targeted e volution (CREATE) to isolate AAV9 variants, such as AAV-PHP.B and AAV-PHP.eB, which can efficiently bypass BBB and transduce the majority of adult brain neurons and astrocytes in certain mouse strains (Chan et al, 2017; Deverman et al, 2016). Both AAV-PHP.B and AAV-PHP.eB have been successfully used to deliver systemic gene expression (Liu et al, 2021; Luoni et al, 2020; Silva-Pinheiro et al, 2020), or target gene ablation by CRISPR/Cas9 across the adult mouse brain neurons (Torregrosa et al, 2021; Xiao et al, 2021; Yamaguchi and de Lecea, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with intravascular administration, ICV injections, like other intracerebrospinal fluid routes of delivery, offer advantages in translational feasibility for CNS disorders: low doses that more readily scale from preclinical models to human, improved efficiency of CNS transduction, and the avoidance of circulating anti-AAV neutralizing antibodies (34)(35)(36). PHP.B yields robust CNS transduction via the ICV route, at least on par with the parent AAV9 capsid (37), but grants superior CNS access when delivered intravascularly in mice (30), offering greater flexibility for future preclinical studies. Following ICV delivery of 1 μL of 1.6 × 10 14 vector genomes (vg)/mL of PHP.B/hUBE3Aopt vector to neonatal AS model mice, which come to lack neuronal expression of UBE3A (38), we performed quantitative PCR (qPCR) analysis of whole-brain RNAs.…”
Section: Resultsmentioning
confidence: 99%
“…AAV vectors have been directly injected into numerous brain regions to edit neuronal proteins [42][43][44][45][46] , including in rodent models of Huntington's disease 47,48 and Alzheimer's disease 49 . Intracerebroventricular (ICV) delivery of AAV carrying CRISPR has been explored to maximize the area of genome editing in the brain due to distribution in the cerebrospinal fluid (CSF) 16,17 . A recent study utilizing ICV delivery of AAVs showed knockdown of NeuN in multiple CNS regions 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Particles with smaller sizes and neutral charges are advantageous for brain editing, as they can diffuse over longer distances in this unique extracellular matrix [11][12][13] . Viral or plasmid vectors have been successfully applied for in vivo delivery of Cas9 and single guide RNA (sgRNA) to the brain, most commonly through the use of adeno-associated virus (AAV) vectors [14][15][16][17][18] . To deliver genome editing components, AAVs depend on the host transcriptional and translational machinery of the cell to generate genome editing ribonucleoproteins (RNPs).…”
Section: Introductionmentioning
confidence: 99%